Survival analysis of mandibular complete dentures with acrylic‐based resilient liners. (21st May 2012) - Kimoto, Suguru; Kimoto, Katsuhiko; Murakami, Hiroshi; Gunji, Atsuko; Ito, Nana; Kawai, Yasuhiko
Abstract : doi: 10.1111/j.1741‐2358.2012.00658.x Survival analysis of mandibular complete dentures with acrylic‐based resilient liners Objective: The purpose of this long‐term randomised controlled trial was to compare the longevity of dentures constructed using a conventional acrylic resin (CAR) to that of dentures constructed using an acrylic‐based resilient liner (ARL). Materials and methods: The follow‐up study was essentially carried out by annual telephone calls to each of the 67 participants. The Kaplan–Meier method and life‐table analysis were used for univariate analyses. The Cox proportional‐hazards test was used as a final model for statistically adjusting predictor variables such as sex, clinician type, mandibular denture type and age at denture delivery. Results: The denture type was likely to affect the survival time of the dentures, while the sex and clinician type were not. The group using acrylic‐based resilient denture liners had twice the risk of having shorter denture‐survival times than those using conventional acrylic resin dentures. Younger participants were likely to have a reduced risk of having shorter denture‐survival times than older participants. Conclusion: We conclude that mandibular complete dentures constructed using ARL are twice as likely as dentures constructed using CAR to have shorter denture survival times, mainly because of material deterioration.